2004
DOI: 10.1257/0002828041302244
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Teachers on Student Achievement: Evidence from Panel Data

Abstract: In order to provide accurate estimates of how much teachers affect the achievement of their students, this study used panel data covering over a decade of elementary student test scores and teacher assignment in two contiguous New Jersey school districts. The test score data, which spanned the years 1989-1990 to 2000-2001, came from nationally standardized basic skills reading and math tests. Data were also collected on students' gender, ethnicity, special education classification, and English as a Second Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
1,210
11
71

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,720 publications
(1,390 citation statements)
references
References 10 publications
56
1,210
11
71
Order By: Relevance
“…However, Rosenholtz's (1986) study showed that positive effects of teaching experience were effective only during the first five years of teaching, but after five years of teaching, the positive effects seemed to diminish. Similar to the results of the Rosenholtz study, in the meta-analytic study by Goe, two studies (i.e., Rockoff, 2004;Hanushek et al, 2005) showed a positive relationship between student math achievement and teaching experience at the elementary and middle school levels but also only for the first few years. However, three other studies analyzed by Goe (i.e., Harvison & Hanushek, 1992;Gallagher, 2004;Carr, 2006) showed a non-significant relationship between teaching experience and student math achievement.…”
Section: Math Teacher Quality and Student Achievement In Mathematicssupporting
confidence: 54%
See 1 more Smart Citation
“…However, Rosenholtz's (1986) study showed that positive effects of teaching experience were effective only during the first five years of teaching, but after five years of teaching, the positive effects seemed to diminish. Similar to the results of the Rosenholtz study, in the meta-analytic study by Goe, two studies (i.e., Rockoff, 2004;Hanushek et al, 2005) showed a positive relationship between student math achievement and teaching experience at the elementary and middle school levels but also only for the first few years. However, three other studies analyzed by Goe (i.e., Harvison & Hanushek, 1992;Gallagher, 2004;Carr, 2006) showed a non-significant relationship between teaching experience and student math achievement.…”
Section: Math Teacher Quality and Student Achievement In Mathematicssupporting
confidence: 54%
“…The synthesis study by Goe reported a positive relationship between teaching experience and math at the elementary and middle school levels (i.e., Rowan, Chiang, & Miller, 1997;Cavalluzzo, 2004;Hanushek, Kain, O'Brien, & Rivkin, 2005;Rockoff, 2004). Additionally, the study by Clotfelter et al (2007) found that teaching experience was a critical factor that contributed to the improved student math scores of all 3rd through 5th grade students in North Carolina.…”
Section: Math Teacher Quality and Student Achievement In Mathematicsmentioning
confidence: 99%
“…Assuming that a standard deviation in the outcome is about 1.5 grade-level equivalents (based on estimates from Meyer, Ory, and Hinckley, 1983), this represents about a fifth of a standard deviation. To put the finding in context, this effect size estimate is roughly twice what many studies find to be the difference in effect between a high-performing and an underperforming teacher (e.g., Aaronson et al, 2007;Kane and Staiger, 2005;Rivkin et al, 2005;Rockoff, 2004). 5 The estimate is based on only three studies.…”
Section: Results: Effects Of Computer-assisted Correctional Educationmentioning
confidence: 83%
“…The treatment causes an increase in total grade points by about 0.30 standard deviations in this group, where these students both complete more courses and improve their grade average. To put the size of the main effect in context, we note that it is comparable to the effect of: a one standard deviation improvement in teacher quality (Rockoff, 2004); a one standard deviation in university class size (Bandiera et al, 2010); and substantial individual incentives for academic performance in college (Angrist et al, 2009), which all have been shown to improve academic performance by about 0.15 standard deviations.…”
Section: Resultsmentioning
confidence: 99%